Justice-restoring responses: a theoretical framework for understanding citizen complaints against the police - McLean, Kyle (Policing and society, 2021)
In an effort to provide a theoretical framework for understanding citizens’ decisions to complain about the police, this paper suggests that citizen complaints can be viewed as a justice-restoring response and tests six hypotheses using a factorial vignette experiment. The findings indicate that individuals are more likely to complain when they perceive the interaction as procedurally unfair, distributively unfair, and when the outcome is unfavourable. Positive pre-existing attitudes towards the police result in an increased likelihood of engaging in a justice-restoring response. Despite drawing on Tyler’s legitimacy theory, these findings differentiate justice-restoring responses from legitimacy by the comparatively greater impact of outcome favourability and the differing direction of the effect of pre-existing attitudes towards the police.